Upscaling cultivation of Saccharina latissima on net or line systems; comparing biomass yields and nutrient extraction potentials - Boderskov, Teis; Rasmussen, Michael Bo; Bruhn, Annette (Frontiers in Marine Science, 2023)
Production of sugar kelp, Saccharina latissima, has the potential of extracting nutrients and carbon from the seawater and returning it to land as a bioresource. The production thereby acts as an emission capture and utilization instrument contributing to mitigation of eutrophication and climate change. To achieve higher biomass yields improving the effects on climate and environment, and the economic feasibility of the production, cultivation techniques need to be optimized. In Denmark so far, S. latissima production yields have been lower than yields documented from Norway and the Faroe Islands. Use of alternative cultivation infrastructure designs with a higher line density per area, and better understanding the effects of annual and seasonal variations in abiotic parameters on growth, could lead the way towards a future higher yield of the S. latissima production. In this study, S. latissima was cultivated in a Danish commercial scale cultivation site for two consecutive seasons comparing the yields of different cultivation techniques: cultivation on nets and a multi-layer single line system, while also testing the possibility of coppicing the blades instead of applying a full harvest. Biomass yields of 5.0 - 6.8 kg FW m-1 cultivation line year-1, and 10.9 – 30.4 kg FW m-2 net structure were achieved. Biomass production, nutrient and carbon extraction potentials up to 91.3 t FW, 110 kg N, 13.1 kg P and 5.1 t C ha-1 were obtained using net cultivation systems and a 1.5 years growth period. Depth of cultivation had a significant effect on yield, but no effect on dry matter, C, N or P contents of S. latissima in a multi-layered line system. Biomass yields from the same system and site varied with a factor of four between years. The use of coppicing enabled multiple harvests of S. latissima, providing however biomass of reduced quality in the second year. This study demonstrates that the production yield of S. latissima can be increased by optimizing cultivation infrastructure, and indicates that net systems, or other cultivation systems with a high line density in the upper water column, can be a means to increase the areal yield of S. latissima.